Folk Games in the Context of the Problem of Enrichment of Mental Development of the Child - Mehri Achilovna, Narbasheva (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the role of the developing function of folk games in the mental development of a child, based on the Uzbek folk game “Besh Tosh (Five Stones).” The study showed that archaic folk games (including the game of pebbles) are one of the generalized forms of historically developed social experience, presented in the form of plot-role and symbolic content, and the systematic conduct of the game of pebbles is very important for the formation of sensorimotor coordination and operational skill.